Maximizing Multiple Intelligences for Unprecedented Academic Achievement - Maspul, Kurniawan Arif (Edutech Publishing Media, 2023)
This study explores the integration of multiple intelligences and enhancing student motivation in Indonesian classrooms. Individual diversity is respected, inclusive education is promoted, student engagement is maximized, and academic motivation is increased. Educators may develop engaging learning environments that respond to students' talents and interests by identifying and integrating multiple intelligences. To collect perspectives from educators, students, and stakeholders, the study used qualitative approaches such as interviews and observations. According to the findings, using multiple intelligences improves student engagement and academic accomplishment. However, issues such as teacher training and assessment systems must be addressed. Collaboration among educators, policymakers, and stakeholders is critical for implementation success. Indonesia can develop a dynamic and empowering educational system that releases students' full potential by integrating multiple intelligences and local expertise.